Pembelajaran Multisensori bagi Siswa Disleksia: Analisis Film Taare Zameen Par dan Implikasinya di Sekolah Dasar - Maisaroh, Siti; Arifah, Nurdiana (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
Dyslexia is a learning disorder that impairs the ability to read and comprehend written information normally. This study aims to examine the application of a multisensory approach in the learning process of dyslexic students at SLB N Bugih Pamekasan. A qualitative method was employed, with data collected through observation, interviews, and documentation. The findings indicate that the use of visual, auditory, and kinesthetic media, along with individualized teaching strategies, effectively enhances students’ learning motivation, active engagement, and comprehension. Teachers actively adapt instructional methods according to each student’s pace and needs. The success of this approach is supported by parental involvement in home learning, teacher training on multisensory techniques, and the availability of supportive classroom facilities. However, challenges include limited appropriate media and aids, as well as insufficient understanding among some teachers regarding dyslexia characteristics. This study emphasizes the importance of developing multisensory teaching modules, ongoing teacher training, and expanding research to other schools. Furthermore, it recommends longitudinal studies and the utilization of digital technology as multisensory learning strategies to strengthen inclusive education responsive to the needs of dyslexic students.